2008
DOI: 10.1016/j.bmc.2008.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peptide-aldehyde inhibitors using R188I mutant of SARS 3CL protease as a proteolysis-resistant mutant

Abstract: The 3C-like (3CL) protease of the severe acute respiratory syndrome (SARS) coronavirus is a key enzyme for the virus maturation. We found for the first time that the mature SARS 3CL protease is subject to degradation at 188Arg/189Gln. Replacing Arg with Ile at position 188 rendered the protease resistant to proteolysis. The R188I mutant digested a conserved undecapeptide substrate with a K(m) of 33.8 microM and k(cat) of 4753 s(-1). Compared with the value reported for the mature protease containing a C-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…[1][2][3] The key enzyme in the processing of polyproteins pp1a and pp1ab, translated by the viral RNA genome of SARS-CoV is called a 3C-like protease (3CL protease). 10 Although our group additionally found that tetrapeptide aldehyde Ac-Thr-Val-Cha-His-H (1) showed high inhibitory activity with an IC 50 value of 98 nM against SARS 3CL R188I mutant protease in 2008, 12 there are generally enzymatic digestions of peptide chains and a-proton racemization. For this reason, a variety of 3CL protease inhibitors have been reported in the literature over the past decade.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[1][2][3] The key enzyme in the processing of polyproteins pp1a and pp1ab, translated by the viral RNA genome of SARS-CoV is called a 3C-like protease (3CL protease). 10 Although our group additionally found that tetrapeptide aldehyde Ac-Thr-Val-Cha-His-H (1) showed high inhibitory activity with an IC 50 value of 98 nM against SARS 3CL R188I mutant protease in 2008, 12 there are generally enzymatic digestions of peptide chains and a-proton racemization. For this reason, a variety of 3CL protease inhibitors have been reported in the literature over the past decade.…”
Section: Introductionmentioning
confidence: 91%
“…At three step sequence for the protection of active functionalities with amine, carboxylic acid and hydroxy groups of (2R,3S)-PIS, gave the protected PIS derivative (6) in 64% yield over 3 steps. Thus, a variety of the coupling reagents was employed between the PIS derivative (9) with a large steric hindrance and cinnamic acid, it was difficult to improve the chemical yields of the corresponding ester (10). Deprotection of the Cbz group of 7 by hydrogenolysis and coupling between the resultant amino group and cinnamic acid with DMT-MM/DIPEA successfully proceeded to afford the cinnamoyl derivative (8) in satisfactory yield.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the kinetic parameters were determined at a constant substrate concentration, and the inhibitor concentrations were varied to assess the K i values [22]. The IC 50 values were determined only for certain potent inhibitors, based on the apparent decrease in the substrate concentration (H-Thr-Ser-Ala-Val-Leu-Gln-Ser-Gly-Phe-Arg-Lys-NH 2 ) upon digestion by R188I SARS 3CL pro , as described previously [19,34]. The cleavage reaction was monitored by analytical HPLC, and the cleavage rates were calculated from the decrease in the substrate peak area.…”
Section: Biological Activitymentioning
confidence: 99%
“…The stability of the SARS 3CL-R188I mutant protease makes it possible to evaluate the inhibitors quantitatively. 43) A substrate-based peptide aldehyde, Ac-ThrSer-Ala-Val-Leu-Gln-H, was selected as the starting compound, and the optimum side chain structure of the potent inhibitor by both peptide aldehyde synthesis methodology with thioacetal and X-ray crystallographic analyses was found to be tetrapeptide aldehyde, Ac-ThrVal-Cha-His-H, which showed the high inhibitory activity, with an IC 50 value of 98 nM toward SARS 3CL-R188I mutant protease. 44 inhibitor, Ac-Thr-Ser-Ala-Val-Leu-Gln-H, at the P1 and P2 sites with the protease appeared to be remarkably effective, and further modification of the small nonpeptide inhibitor is now underway (Fig.…”
Section: Synthesis and Evaluation Of Peptide Aldehyde-type Inhibimentioning
confidence: 99%